Reconciliation Between the Victim and the Perpetrator-Restorative Justice - Aliu Albana; Arifi Besa (SEEU Review, 2021)
The purpose of this research is to study and address the relation between the perpetrator and the victim, in particular the way it is regulated in the Republic of Kosovo by comparing it with the regulation in other countries. A long time ago criminal law in its institutes has paid attention only to the perpetrator, trying to guarantee his fundamental rights, it is enough to stop at the institute of presumption of innocence and many other institutes and we can see how importance criminal law and in particular criminal procedure has paid to the perpetrator, and on the other hand the victim has always remained in the shadows.